Zur Bedeutung der räumlichen Mobilität in einer Währungsunion - Peter Rühmann (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2009)
There seems to exist a consensus that transnational labour mobility will help to equalize workers` incomes and domestic product per head between the member countries of a monetary union. However, the the new economic geography` which stresses the centrifugal spatial forces of economic activity cast doubts on this opinion. By contrasting neoclassical analysis with models of imperfect competition, this paper illustrates the view that labour mobility might aggravate as well as equalize the national differences in domestic product per head. Therefore, with respect to EMU, it seems reasonable to support forms of transnational mobility which avoid the potential polarizing effects as far as possible.
Keywords: F22; F33; 330; Transnational Labour Mobility; European Monetary Union